miRNA and Proteomic Dysregulation in Non-Small Cell Lung Cancer in Response to Cigarette Smoke - Babu, Niraj; Advani, Jayshree; Solanki, Hitendra S.; Patel, Krishna; Jain, Ankit; Khan, Aafaque A.; Radhakrishnan, Aneesha; Sahasrabuddhe, Nandini A.; Mathur, Premendu Prakash; Nair, Bipin; Keshava Prasad, Thottethodi Subrahmanya; Chang, Xiaofei; et al. (MicroRNA, 2018)
Background: Dysregulation of miRNAs is associated with the development of non-small cell lung cancer (NSCLC). It is imperative to study the dysregulation of miRNAs by cigarette smoke which will affect their targets, either leading to the overexpression of oncoproteins or downregulation of tumor suppressor proteins. Objective and Methods: In this study, we carried out miRNA sequencing and SILAC-based proteomic analysis of H358 cells chronically exposed to cigarette smoke condensate. Using bioinformatics analysis, we mapped the dysregulated miRNAs to differentially expressed target proteins identified in our data. Gene ontology-based enrichment and pathway analysis was performed using the deregulated targets to study the role of cigarette smoke-mediated miRNA dysregulation in NSCLC cell line. Results: miRNA sequencing resulted in the identification of 208 miRNAs, of which 6 miRNAs were found to be significantly dysregulated (2 fold, Log Base 2; p-value ≤ 0.05) in H358-Smoke cells. Proteomic analysis of the smoke exposed cells compared to the untreated parental cells resulted in the quantification of 2,610 proteins, of which 690 proteins were found to be differentially expressed (fold change ≥ 2). Gene ontology based analysis of target proteins revealed enrichment of proteins driving metabolism and a decrease in expression of proteins associated with immune response in the cells exposed to cigarette smoke. Pathway study using Ingenuity Pathway Analysis (IPA) revealed activation of NRF2-mediated oxidative stress response and actin-cytoskeleton signaling, and repression of protein kinase A signaling in H358-Smoke cells. We also identified 5 novel miRNAs in H358-Smoke cells using unassigned reads of small RNA-Seq dataset. Conclusion: In summary, this study indicates that chronic exposure to cigarette smoke leads to widespread dysregulation of miRNAs and their targets, resulting in signaling aberrations in NSCLC cell line. The miRNAs and their targets identified in the study need to be further investigated to explore their role as potential therapeutic targets and/or molecular markers in NSCLC especially in smokers.
Keywords: cigarette smoke